Abdominal Obesity as a Mediator of the Influence of Physical Activity on Insulin Resistance in Spanish Adults - Garcia-Hermoso, A (Academic Press, 2016)
Objective: The aim of the study was to analyze the relationship between moderate-to-vigorous physical activity (MVPA) and insulin resistance (IR) in Spanish adults and to examine whether this relationship is mediated by abdominal obesity (waist circumference - WC). Methods: The cross-sectional study included 1162 healthy subjects belonging to the EVIDENT study (mean age 55.0 ± 13.3 years; 61.8% women) from six different Spanish provinces. Moderate-to-vigorous physical activity (MVPA) was measured objectively over 7 days using Actigraph accelerometers, collecting data in 60-second epochs, and retaining respondents with ≥. 4 valid days for the analysis. The homeostasis model of assessment (HOMA-IR) was used to determine IR, and its individual components - fasting glucose and insulin - were determined using standard protocols. Linear regression models were fitted according to Baron and Kenny s procedures for mediation analysis. Results: Fasting insulin and HOMA-IR levels were significantly worse in adults who spent fewer minutes in MVPA (first quartile ≤ 30.1 and 22.7 min/day in men and women, respectively) after adjusting for age, sex, smoking habits, drinking habits, accelerometer wear time, sedentary time, and Mediterranean diet adherence. However, when WC was added to the ANCOVA models as a covariate, the effects disappeared. Mediation analysis reported that WC acts as a full mediator in the relationship between MVPA and IR (HOMA-IR and fasting insulin). Conclusion: These findings show that WC plays a pivotal role in the relationship between MVPA and IR, and therefore highlights that decreasing abdominal obesity might be considered as an intermediate outcome for evaluating interventions aimed at preventing diabetes mellitus. © 2015 Elsevier Inc.
Keywords: Diabetes; Moderate-to-vigorous physical activity; Obesity; Waist circumference; Obesity; Cardiometabolic risk factors